Failure Mechanism and Control Technology for a Large-Section Roadway under Weakly Cemented Formation Condition - Jiadi Yin; Baojie Fu; Hualei Zhang (Geofluids)
The roof of a large-section roadway will usually undergo progressive deformation and failure under the action of deep surrounding rock stress. The large-section rectangular roadway is more prone to sudden roof caving accident under the weakly cemented formation condition, which poses great threats to operating personnel and mechanical equipment and brings about considerable difficulties to roof monitoring and evaluation. A large-scale caving accident that occurred on a large-section rectangular roadway in Bojianghaizi Mine in Inner Mongolia was taken as the study object. The factors that triggered the roadway roof caving were analyzed by investigating the roof caving mechanism of weakly cemented overlying strata, and an effective roof supporting method was proposed. A numerical mechanical analysis model was established for surrounding rocks of the roadway by using the discrete element method, and numerical simulation results showed that obvious vertical cracks would be generated at two ends of the roof under the action of shearing stress. With upward crack propagation and transverse crack penetration at the roof separation, a dangerous caving zone penetrated by cracks formed inside the roof. The permeation of the upper aquifer would reduce the rock strata strength at the roof and further aggravate the risk of roadway caving. In accordance with the numerical simulation and comprehensive analysis of field exploration data, the main reasons for the roadway caving accident were concluded as follows: (1) low rock strata strength at the roof and the influence of tectonic stress in deep surrounding rocks, (2) unreasonable original support pattern, and (3) permeation of the upper aquifer. On this basis, an improved support scheme was proposed, and field monitoring data showed that the maximum separation amount of the roof was controlled at 14 mm, and the roof deformation was well controlled, thus meeting the safety production requirements. The proposed method can provide a reference for the control of weak roadway roof and its support scheme design.